2017
DOI: 10.1016/j.trecan.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Metabolism in Cancer: Understanding the Heterogeneity

Abstract: Reliance on glutamine has long been considered a hallmark of cancer cell metabolism. However, some recent studies have challenged this notion in vivo, prompting a need for further clarifications on the role of glutamine metabolism in cancer. We find that there is ample evidence of an essential role for glutamine in tumors and that a variety of factors, including tissue type, the underlying cancer genetics, the tumor microenvironment and other variables such as diet and host physiology collectively influence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
413
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(422 citation statements)
references
References 103 publications
8
413
0
1
Order By: Relevance
“…41,42 Studies have shown glutamine metabolism reprogramming in a tissue-dependent and tumor-heterogeneous manner. 43 Its role in disparities remains to be investigated. Lysine catabolism is important in the early stages of liver metastasis in colorectal cancer, but it is not essential for growth in liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Studies have shown glutamine metabolism reprogramming in a tissue-dependent and tumor-heterogeneous manner. 43 Its role in disparities remains to be investigated. Lysine catabolism is important in the early stages of liver metastasis in colorectal cancer, but it is not essential for growth in liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The amide nitrogen of glutamine is most often used to synthesize asparagine and nucleotide, concomitantly with production of glutamate (27). Glutamate can be used for multiple purposes, but it can be readily synthesized through the transamination between α-ketoglutarate and other amino acids, thus it is dispensable to cancer cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported that lower levels of amino acids may be related to a higher protein demand in cancer cells to support their rapid growth and proliferation . During glutaminolysis, a central distinctive feature of cancer metabolism, glutamate converts glutamine to α‐ketoglutarate, which is introduced into the tricarboxylic cycle to produce energy and anabolic carbons for the synthesis of amino acids, nucleotides, and lipids . Although no significant alterations in glutamine concentrations in primary breast cancer patient plasma were observed, its interchangeable substrate, glutamate, was found at significantly lower concentrations in primary breast cancer patients compared to those in healthy controls.…”
Section: Discussionmentioning
confidence: 98%